A unique chromosome translocation disrupting ClWIP1 leads to gynoecy in watermelon. (17th October 2019) - Zhang, Jie; Guo, Shaogui; Ji, Gaojie; Zhao, Hong; Sun, Honghe; Ren, Yi; Tian, Shouwei; Li, Maoying; Gong, Guoyi; Zhang, Haiying; Xu, Yong
Summary: To understand sex determination in watermelon ( Citrullus lanatus ), a spontaneous gynoecious watermelon mutant, XHBGM, was selected from the monoecious wild type XHB. Using map‐based cloning, resequencing and fluorescence in situ hybridization analysis, a unique chromosome translocation between chromosome 2 and chromosome 3 was found in XHBGM. Based on the breakpoint location in chromosome 2, a putative C2H2 zinc finger transcription factor gene, ClWIP1 (gene ID Cla008537 ), an orthologue of the melon gynoecy gene CmWIP1, was disrupted. Using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated system 9 to edit ClWIP1, we obtained gynoecious watermelon lines. Functional studies showed that ClWIP1 is expressed specifically in carpel primordia and is related to the abortion of carpel primordia in early floral development. To identify the cellular and metabolic processes associated with ClWIP1, we compared the shoot apex transcriptomes of two gynoecious mutants and their corresponding wild types. Transcriptome analysis showed that differentially expressed genes related to the ethylene and cytokinin pathways were upregulated in the gynoecious mutants. This study explores the molecular mechanism of sex determination in watermelon and provides a theoretical and technical basis for breeding elite gynoecious watermelon lines. Significance Statement: We found a unique chromosome translocation in the spontaneous gynoecious watermelon mutant XHBGM that disrupted the ClWIP1 gene and created artificial gynoecious watermelon lines using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated system 9 to edit the ClWIP1 gene. Transcriptome analysis suggests that the ethylene and cytokinin pathways mediate development of the pistil primordium. This study explores the molecular mechanism of sex determination in watermelon and provides a technical basis for breeding gynoecious watermelon lines for hybrid seed production.